ANALYSIS OF THE GOOD AND CORRECT USE OF INDONESIAN LANGUAGE IN INDONESIAN OLYMPIC NEWS STORIES BY METRO TV AUGUST 11 2024 EDITION - Yuni ertinawati; Putri Kurniawan, Intania; Saputra, Muhammad Ridwan; Annisa, Qeilla Fuji (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
In the era of growing information, mass media has a crucial role in delivering news, especially related to athletes' achievements in major events such as the Olympics. This article analyzes the use of good and correct language in the Indonesian Olympic news broadcast by Metro TV on August 11, 2024. This research uses a qualitative method with documentation techniques to identify the use of sports terms, ineffective sentences, and absorbed words. The results of the analysis show that although there is a standardized use of technical terms, there are still many ineffective sentences and the use of nonstandard language that interfere with the credibility of the news. This article contributes to the understanding of the importance of formal language use in the media context, and provides recommendations to improve the quality of news delivery in the mass media. Through this research, it is hoped that public awareness of the use of good and correct language can increase, in line with efforts to strengthen the nation's cultural identity in the midst of globalization.